2019
DOI: 10.18488/journal.aefr.2019.95.559.580
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Operational Efficiency of Pakistani and Malaysian Islamic Banks: Data Envelopment Analysis Approach

Abstract: This study compares the execution and potency of the Islamic banking operations currently practiced by Pakistan and Malaysia Islamic banks. In the 1980s both countries embarked their work on the Islamic banking system by using different entirely approaches. Malaysia adopted moderate solicitations towards the implementation of the Islamic financial system according to the shariah and law, which allows Islamic and the conventional banking system to operate on a parallel basis. On the other side, Pakistan engaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…In simpler terms, it suggests that the money the government owes, domestically and internationally, doesn't significantly affect the country's ability to grow economically. Haider, Raza, Jameel, and Pervaiz (2019); Siddique, Ullah, and Haq (2017) assessed the impact of Pakistan's leaping foreign debt crisis on the country's economy. The outcomes of this study showed that while foreign debt has a considerable and negative impact on GDP growth, trade, and human capital are two factors that can contribute to economic growth.As per Awan and Qasim (2020), imports, debt services, external debt, and population growth rate, all these factors have an inverse relation to the GDP growth of Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In simpler terms, it suggests that the money the government owes, domestically and internationally, doesn't significantly affect the country's ability to grow economically. Haider, Raza, Jameel, and Pervaiz (2019); Siddique, Ullah, and Haq (2017) assessed the impact of Pakistan's leaping foreign debt crisis on the country's economy. The outcomes of this study showed that while foreign debt has a considerable and negative impact on GDP growth, trade, and human capital are two factors that can contribute to economic growth.As per Awan and Qasim (2020), imports, debt services, external debt, and population growth rate, all these factors have an inverse relation to the GDP growth of Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These banks also confront challenges in consumer lending and government budget funding. The profit and loss sharing mode of finance is one of the key spirits of Islamic banking but due to the risk in this mode of finance, practically all Islamic banks in Pakistan are engaged in providing a consistent return (Haider, 2019). The Islamic banking sector has experienced enormous expansion, particularly in Islamic nations, with GCC countries and Malaysia leading the way.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…En estudios previos se aplican los tipos de frontera de producción de la banca con base en apreciaciones sobre su comportamiento más probable o sin probar cuál predomina (Haider et al, 2019;Korneyev et al, 2022;Sarmiento et al, 2018;Shi et al, 2023). Incluso, Henriques et al (2018) emplean tanto el modelo RCE como el de RVE, afirmando que en la literatura especializada no hay consenso sobre cuál modelo es mejor para evaluar las instituciones financieras.…”
Section: Sistema De Hipótesisunclassified
“…En otros contextos ajenos a Latinoamérica, como en la banca de Malasia, se han reportado valores ligeramente diferentes de ETG (0.908), ETP (0.994) y EE (0.912), así como en Paquistán: ETG = 0.947, ETP = 0.996 y EE = 0.950 (Haider et al, 2019), lo cual sería consistente con una banca globalizada.…”
Section: Issn Online 2007-9621unclassified